Hot deformation and dynamic recrystallization behavior of TiAl-based alloy. (September 2019) - Tian, Shiwei; Jiang, Haitao; Guo, Wenqi; Zhang, Guihua; Zeng, Shangwu
Abstract: Hot compression and dynamic recrystallization (DRX) behavior of TiAl alloy (Ti-44Al-4Nb-1.0Mo-0.1B-0.01Y) were investigated by hot compression tests. The tests were conducted at temperature range of 1120–1240 °C with strain rate of 10 −3 ∼1 s −1 . Results show that the flow stress during hot compression is affected by deformation temperature and strain rate. The stress exponent n and activation energy Q are measured to be 2.711 and 524.67 kJ/mol, respectively. Critical strain for DRX initiation is measured, and the relationship between critical strain ε c and peak strain ε p can be expressed as: ε c = (0.7–0.9) ε p . It is found that crack in β phase as well as the decomposition of β phase result from inhomogeneous deformation between γ phase and β phase. With the decreasing of ln Z, volume fraction (referred to V f ) of lamellar colony decreases and α phase gradually "invade" from the periphery to the center part of lamellar colony. Two DRX models during the hot deformation of TiAl alloy are developed. Type I relies on the nucleation within lamellae. Type II is the DRX of α phase. If ln Z >39.6, only type I can be found in the microstructure. If 36.1<lnZ<39.6, the microstructure contains the mixture of type I and type II DRX grains. While lnZ<36.1, only type II DRX grains are left. The guiding principle can well predict the deformed microstructure of TiAl alloy. Graphical abstract: There are two DRX models during the hot deformation of TiAl alloy. Type I relies on the nucleation in the lamellae. Type II is the DRX of α phase. If ln Z ＞39.6, only type I can be found in the microstructure. The shape of lamellae colony remains intact. If 36.1＜lnZ＜39.6, the microstructure contains the mixture of type I and type II DRX grains. With the decreasing of ln Z, α phase gradually "invade" from the periphery to the center part of lamellae. While ln Z ＜36.1, only type II DRX grains were left and α phase becomes the main phase. The judging principle can well predict the deformed microstructure of TiAl alloy.Image 1 Highlights: Cracks in β phase and the decomposition of β phase result from inhomogeneous deformation between γ phase and β phase. The relationship between critical strain εc and peak strain εp can be expressed as: εc = (0.7~0.9) εp . EBSD result confirm that γ phase is easier to DRX than the α phase. Two DRX models are observed. Type I relies on the nucleation within lamellae. Type II is the DRX of α phase. The relationship among ln Z, DRX model and microstructure is built, which can well predict the deformed microstructure.